Price Caps, Efficiency Payoffs, and Infrastructure Contract Renegotiation in Latin America - Estache, Antonio; Guasch, Jose-Luis; Trujillo, Lourdes (World Bank, Washington, DC, 2014)
Twenty years ago, as the United Kingdom was getting ready to launch the privatization of its public services, Professor Littlechild developed and operationalized the concept of price caps as a regulatory regime to control for residual monopoly conditions in those services. Ten years later, Latin American countries, as they embarked into their own infrastructure reforms, also adopted the price cap regulatory model. Relying on a large data base on the factors driving contract renegotiation in the region and a survey of the literature on efficiency gains, the authors assess the impact of this regulatory regime in Latin America. They show that while the expected efficiency gains were amply achieved, these gains were seldom passed on to the users. Instead they were shared by the government and the firms. Moreover, the adoption of price caps implied higher costs of capital and hence, tariffs, and brought down levels of investment.